Equations for mix design of structural lightweight concrete - Abdullahi M. (EuroJournals, Inc., 2023)
Equations for mix design of structural lightweight concrete are presented. Conventionally, mix design of concrete is conducted using the tabular data and charts in standards. This requires extra efforts of understanding the data in the code and interpolations are often required when intermediate values are needed. The process is also liable to human error as data may be erroneously taken by the mix designer. The tabular data and graphs in ACI 211.2-98 are converted to equations. Various models were tried and the best model that adequately represents the data was chosen based on the regression coefficient and its predictive capability. The equations were used to solve some mix design problems from reputable textural sources. The developed equations are capable of giving material constituents for the first trial batch of structural lightweight concrete. These equations can be used in place of the data in the code and would reduce the effort, time and energy expended in the manual process of mix design of structural lightweight concrete. The equations are also useful for mixture proportioning adjustment. EuroJournals Publishing, Inc. 2009.